Cardiovascular Regulation by the Neuronal BBSome. Issue 4 (April 2020) - Guo, Deng-Fu; Reho, John J.; Morgan, Donald A.; Rahmouni, Kamal
Abstract : The BBSome, a complex of 8 BBS (Bardet-Biedl syndrome) proteins known for its role in the control of cilia function and other cellular processes, has been implicated in blood pressure control, but the underlying mechanisms are not fully understood. Here, we show that neuronal BBSome plays an important role in blood pressure regulation. Targeted inactivation of the BBSome in the nervous system through Bbs1 gene deletion causes sympathetically mediated increase in blood pressure in mice. This phenotype is reproduced by selective ablation of the Bbs1 gene from the LRb (leptin receptor)-expressing neurons. Strikingly, the well-known role of the BBSome in the regulation of cilia formation and function is unlikely to account for the prohypertensive effect of BBSome inactivation as disruption of the IFT (intraflagellar transport) machinery required for ciliogenesis by deleting the Ift88 gene in LRb neurons had no effect on arterial pressure and sympathetic nerve activity. Furthermore, we found that Bbs1 gene deletion from AgRP (agouti-related protein) neurons or POMC (proopiomelanocortin) neurons increased renal and splanchnic sympathetic nerve activity without altering blood pressure. This lack of blood pressure increase despite the sympathetic overdrive may be explained by vascular adrenergic desensitization as indicated by the reduced vascular contractile response evoked by phenylephrine and the decreased expression of adrenergic receptors. Our results identify the neuronal BBSome as a new player in hemodynamic, sympathetic, and vascular regulation, in a manner independent of cilia. Abstract : Supplemental Digital Content is available in the text.